THE RELATIONSHIP BETWEEN FUEL OIL (BBM) LIMITATIONS AND THE INCREASE IN ILLEGAL FISHING BY LOCAL FISHERMEN - Diky Dikrurrahman; Mochamad Hepy Rizkianda; Riyan Hamzah; Rian Anggara Assyarif (Jurnal Abdisci, 2025)
Abstract. Background. The scarcity of fuel oil (BBM) is one of the main factors affecting fishermen's activities in running a fishing business. The fuel crisis impacts the economy and encourages an increase in illegal fishing practices by local fishermen. Aims. This study aims to analyze the relationship between fuel limitations and the increase in illegal fishing activities, the factors that affect them, and mitigation efforts that the government and the authorities can carry out. Methods. This study used a qualitative method with a descriptive approach. Data collection was carried out through in-depth interviews and supported by literature studies to gain a comprehensive understanding of the problems being researched. Result. The results of the study show that the scarcity of fuel oil (BBM) has a significant impact on fishermen's activities in running a fishery business. Conclusion. Fuel limitations increase operational costs, thereby reducing fishermen's income and hindering the sustainability of the fishery business. In addition, this condition encourages some fishermen to practice illegal fishing as a survival strategy due to increasing economic pressure. Implementation. Some of the factors contributing to the increase in illegal fishing due to the fuel crisis include the high price of subsidized fuel, uneven distribution, and the lack of fuel alternatives that fishermen can access.